A Phase II Trial of Stereotactic Ablative Body Radiotherapy for Low-Risk Prostate Cancer Using a Non-Robotic Linear Accelerator and Real-Time Target Tracking: Report of Toxicity, Quality of Life, and Disease Control Outcomes with 5-Year Minimum Follow-Up - Mantz, Constantine (Frontiers in Oncology, 2014)
Purpose/Objective(s): Herein, we report the results of an IRB-approved phase II trial of Varian Trilogy/TrueBeam-based SABR monotherapy for low-risk prostate cancer using the Calypso® System to provide real-time electromagnetic tracking of the prostate’s position during treatment delivery. Materials/Methods: A total of 102 low-risk patients completed protocol treatment between January 2007 and May 2009. A total dose of 40.0 Gy in 5 every-other-day fractions of 8.0 Gy was prescribed to the planning target volume. Target setup and tracking procedures were as follows: (1) the Calypso® System was used to achieve target setup prior to each fraction; (2) conebeam CT imaging was then used for correction of setup error and for assessment of target and Organs-at-Risk (OAR) deformations; (3) after treatment delivery was initiated, the Calypso® System then provided real-time intrafractional target tracking. The NCI CTCAE v3.0 was used to assess urinary and rectal toxicity during treatment and at defined followup time points. Biochemical response and quality of life measurements were made at concurrent followup points. Results: Urinary toxicities were most common. At 6 months, 19.6%, 2.9% and 4.9% of patients reported grades 1 – 2 urinary frequency, dysuria and retention, respectively. Rectal toxicities were uncommon. By 12 months, 2.9% of patients reported painless rectal bleeding with subsequent symptom resolution without requiring invasive interventions. Quality of life measurements demonstrated a significant decline over baseline in urinary irritative/obstructive scores at 1 month following SABR but otherwise did not demonstrate any difference for bowel, bladder and sexual function scores at any other followup time point. One patient suffered biochemical recurrence at 6 years following SABR. Conclusions: At five years minimum followup for this favorable patient cohort, prostate SABR resulted in favorable toxicity, quality of life and biochemical outcomes.